A real-world retrospective, observational study of first-line pembrolizumab plus chemotherapy for metastatic non-squamous non-small cell lung cancer with PD-L1 tumor proportion score < 50% (PEMBROREAL) - Cafaro, Alessandro; Foca, Flavia; Nanni, Oriana; Chiumente, Marco; Coppola, Marina; Baldo, Paolo; Orzetti, Sabrina; Enrico, Fiorenza; Ladisa, Vito; Lerose, Rosa; Nardulli, Patrizia; Maiolino, Piera; et al. (Frontiers in Oncology, 2024)
The phase III Keynote-189 trial established first-line treatment combining pembrolizumab with pemetrexed and platinum as a standard treatment for patients with stage IV NSCLC without known EGFR and ALK driver mutations and independent of PD-L1 expression. However, in Italy, eligibility for the National Health payment program is limited to patients with PD-L1 <50 %. The PEMBROREAL study assesses the realworld effectiveness and safety of pembrolizumab in patients eligible for the National Health Service payment program.Methods: PEMBROREAL is a retrospective, observational study on patients with NSCLC who started pembrolizumab combined with pemetrexed and platinum within the reimbursability time window, considered as December 2019 to December 2020. The primary endpoints were to assess PFS and OS (using the Kaplan-Meier method), response to therapy, and tolerability.Results: Until February 2022, 279 patients (median follow-up 19.7 mo.) have been observed. The median PFS was 8.0 months (95% Confidence interval: 6.5 -9.2). OS was not reached but we can estimate a 12 to 24month survival rate for the combined treatment: 66.1 % and 52.5 % respectively. PDL-1 expression and ECOG performance status were both associated with PFS and OS. Overall, only 44.4% of patients reported an adverse event, whereas toxicity led to a 5.4 % discontinuation rate.The results of the PEMBROREAL study have shown that the combined treatment of pembrolizumab with pemetrexed and platinum is effective for metastatic non-squamous NSCLC, even for patients with PD-L1 levels below 50%, despite the differences in patient demographics and pathological features compared to the Keynote-189 study. The adverse events reported during the study were more typical of chemotherapy treatment rather than immunotherapy, and physicians were able to manage them easily.